Raça, natureza e sociedade: o pensamento evolucionista em Fortaleza na década de 1880 - Fonseca, Jamily Marciano (2015)
The present paper aims to analyse the speeches of the Ceará intellectuals in the 1880s, seeking to understand how the evolutionist ideas were received, as well as their influence on the way of thinking about nature, race and the progress of Brasil and the Ceará province. Ceará intellectuals worked together in several periodicals circulating in its capital, Fortaleza, through which their ideas were spreaded. With the analysis of the sources, namely newspapers, we realize that Justiniano de Serpa, Antonio Martins, João Lopes, Pedro de Queiroz and other intellectuals thought about the society they lived, environment and mankind in general, based upon their theoretical influences. Darwinism, Spencerianism and racialism were some of the evolutionary theories that became popular since the second half of the nineteenth century and contributed to the rise of a worldview that drove many intellectuals around the world to seek explanations for the realities in which they lived and to elaborate progressist solutions aiming the improvement of their society. Our discussion is based on the analysis of texts published in periodicals of Fortaleza in the 1880s, where we perceive the influence of evolutionist thought, seeking to realize how the evolutionist theories were appropriated by intellectuals, as well as to understand their interpretations of Ceará society, mankind and the environment.